Analysis of Public Services at the Dumai City One-Stop Integrated Administration System (SAMSAT) Office - Lilis Wahyuni; Audiva Martin; Nurul Anisa; Puja Fadilah; Wilia Dita Asmara (International Journal of Humanities and Social Sciences Reviews, 2025)
Public service is the primary indicator of the effectiveness of government bureaucratic performance, as it directly reflects how well public institutions meet community needs. This study aims to evaluate the quality of public services at the Dumai City SAMSAT Office using the SERVQUAL approach, which consists of five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The research employed a descriptive qualitative method with a purposive sampling technique. Informants included one SAMSAT employee and two service users selected based on their direct experience with the service process. Data were collected through interviews and observations to gain an in-depth understanding of service implementation. The findings reveal that the tangible, empathy, and responsiveness dimensions have been implemented relatively well, indicated by improved facilities, supportive infrastructure, and faster service delivery. However, weaknesses remain in the reliability and assurance dimensions, particularly regarding service consistency and the professionalism and attitude of officers toward the public. The study recommends strengthening integrated service systems and enhancing ethics and service excellence training for employees to improve overall service quality.